Alcoholism and Elder Abuse - Anetzberger, Georgia J. (Journal of interpersonal violence, 1994)
A comparison group study of abusing and nonabusing caregivers suggested a correlation between alcohol use and abuse and violence against elderly parents. Findings reveal that abusers were more likely than nonabusers to drink, to become intoxicated, and to be identified as having a drinking problem. Policy and practice implications are discussed